The Awkward Imam: Authority and Friction in Turkish Diaspora Mosques - Hartmann, Ida (Journal of Muslims in Europe, 2025)
Focusing on Turkish imams in Europe, this article explores how religious authority travels and translates across geographical distances and cultural differences. Imams are often depicted as influential transnational figures channeling religious and political affect from the "homeland" to the diaspora with little restraint. By contrast, this article explores the manifold layers of "friction" that arise from everyday encounters between Turkish imams and local diasporic communities. Assuming that authority is inherently relational, the article shows how the imam’s authority is challenged from above by his superiors within the Turkish state bureaucracy, from beyond by his lack of cultural literacy within the European context, and from within by the resistance or indifference of local mosque participants. Drawing on 12 months of ethnographic fieldwork, the article focuses on Turkish-Danish mosque-communities but draws the broader tendencies and particularities of this national context into relief through asymmetrical comparison with the UK and Germany.